2004
DOI: 10.4049/jimmunol.173.8.5247
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Proliferation by Direct Cross-Talk between OX40 Ligand on Human Mast Cells and OX40 on Human T Cells: Comparison of Gene Expression Profiles between Human Tonsillar and Lung-Cultured Mast Cells

Abstract: Mast cells (MCs) are the primary effector cells in allergic reactions and have also been found to activate T cells and to reside in close physical proximity to T cells. However, the molecular mechanisms involved in the MC-T cell interaction remain unclear. We hypothesized that human tonsillar MCs, which locate in the interfollicular areas, might interact with T cells. Thus, we first established a culture system of human tonsillar MCs and then compared gene expression profiles of tonsillar MCs with that of lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
120
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 55 publications
8
120
2
1
Order By: Relevance
“…Co-stimulatory molecules expressed by mouse and/ or human mast cells include members of the B7 family, members of tumour-necrosis factor (TNF)-TNF receptor families, CD28 and CD40 ligand (CD40L) 6,13,46,47 . Moreover, mast cells can exhibit costimulatory function in vitro.…”
Section: Mast-cell Immunomodulatory Functions Immunomodulatory Activimentioning
confidence: 99%
See 2 more Smart Citations
“…Co-stimulatory molecules expressed by mouse and/ or human mast cells include members of the B7 family, members of tumour-necrosis factor (TNF)-TNF receptor families, CD28 and CD40 ligand (CD40L) 6,13,46,47 . Moreover, mast cells can exhibit costimulatory function in vitro.…”
Section: Mast-cell Immunomodulatory Functions Immunomodulatory Activimentioning
confidence: 99%
“…Moreover, mast cells can exhibit costimulatory function in vitro. For example, engagement of the costimulatory ligand OX40L expressed by human 46 or mouse 47 mast cells and OX40 expressed by T cells is required for optimal mast-cell-dependent enhancement of T-cell proliferation 46,47 or cytokine production 47 .…”
Section: Mast-cell Immunomodulatory Functions Immunomodulatory Activimentioning
confidence: 99%
See 1 more Smart Citation
“…Although such costimulatory molecules are generally thought to have roles in DC-associated T cell activation, Kashiwakura et al (26) reported that human tonsil mast cell-OX40L can contribute to the T cell proliferation induced when human T cells are incubated with mast cells that have undergone Fc⑀RI-dependent activation in vitro.…”
Section: Ast Cells Represent Important Effector Cells In Th2-andmentioning
confidence: 99%
“…However, certain mast cell populations, in addition to having the capacity to produce soluble factors that can influence T cell biology, can express costimulatory molecules such as OX40 ligand (OX40L) and 4-1BBL (22,26). Although such costimulatory molecules are generally thought to have roles in DC-associated T cell activation, Kashiwakura et al (26) reported that human tonsil mast cell-OX40L can contribute to the T cell proliferation induced when human T cells are incubated with mast cells that have undergone Fc⑀RI-dependent activation in vitro.…”
Section: Ast Cells Represent Important Effector Cells In Th2-andmentioning
confidence: 99%